Molecular insights into Herniarin: Structural, spectroscopic, electronic and thermodynamic characterization via Density Functional Theory - Thapa, Dipak; Rai, Krishna Bahadur; Pandey, Bishal; Ghimire, Madhav Prasad (Himalayan Physics, 2025)
In this study, Herniarin molecule were investigated using Density Functional Theory at the B3LYP/6-311++G(d,p) level. The optimized geometry exhibited energy of -16645.48 eV and a dipole moment of 6.57 Debye, indicating molecular polarity. The calculated bond lengths and angles showed good agreement with experimental data for coumarin analogs. Vibrational analysis confirmed C-H, C-C, C=O, and C-O stretching and bending vibrations within standard ranges. Non-covalent interaction and Reduced Density Gradient analyses revealed steric repulsion and weak van der Waals interactions, with no hydrogen bonding. Electron Localization Function and Localized Orbital Locator mappings showed strong electron localization around hydrogen and oxygen atoms and delocalization within the aromatic ring. Frontier Molecular Orbital analysis yielded HOMO and LUMO energies of -6.46 eV and -2.08 eV, respectively, with an energy gap of 4.38 eV, consistent with the 4.30 eV gap from the Density of States spectrum, confirming molecular stability. Global reactivity descriptors i.e. ionization potential (6.46 eV), electron affinity (2.08 eV), hardness (2.19 eV), and electrophilicity index (4.16 eV) indicated moderate reactivity and chemical stability. Molecular Electrostatic Potential and Electrostatic Potential maps identified oxygen atoms as electron-rich and hydrogen atoms as electron-deficient reactive sites. Mulliken charges analysis showed that all hydrogen atoms carry positive charges, all oxygen atoms carry negative charges, with C3 is the most negatively and C4 is the most positively charge. Thermodynamic parameters i.e. Hom, Som, and Cop,m increased with the rise in temperature (10-500 K), showing strong quadratic correlations (R2 > 0.99), indicated thermal stability and predictable thermodynamic behavior.